فعالية التخطيط المالي ودوره في تطوير المؤسسات الرياضية - بلجود, عبد الرؤوف (My University, 2020)
الملخص : بالعربية إن تصميم هذه الدراسة كان بهدف الوقوف على حقيقة مدى فاعلية التخطيط المالي ودوره في نجاح المؤسسات الرياضية لدى مديرية الشباب والرياضة لولاية المسيلة، ومن ثم تحديد كيفية استخدام أهم الخطوات التي تساعد في إعداد خطة مالية تمكن من نجاح وتطوير المؤسسات الرياضية . ولتحقيق ذلك استخدم الباحث المنهج الوصفي لملائمته لهذه الدراسة على عينة عشوائية فبلغ عددها 30 موظفا من مديرية الشباب والرياضة لولاية المسيلة ، ولتوفير المعلومات التي يمكن الإعتماد عليها في اصدار الأحكام حول فاعلية التخطيط المالي ودوره في نجاح المؤسسات الرياضية تم تطبيق استبيان لذلك ، وبعد التأكد من صدق وثبات الاستبانة ، تم استخدامها ، وبعد ذلك تم جمع وإعداد البيانات النهائية للتحليل الاحصائي _الكلمات المفتاحية : التخطيط المالي، المؤسسات الرياضية. جاء هذا البحث في فصول: تناول: الفصل الأول : يتمثل في «الإطار العام للدراسة» حيث استعرضنا فيه المفاهيم والمصطلحات التي تتعلق بالبحث وتحديد الإشكالية وكيفية صياغتها والتساؤلات الجزئية والابرز الأهداف وتوضيح الأهمية ثم الفرضية العامة و الفرضيات الجزئية والدراسات السابقة والمشابهة. الفصل الثاني :المتمثل في «الخلفية النظرية» تناولنا فيها مفهوم التخطيط المالي وأهميته وأهدافه ومراحله وأنواعه وأدواته. الفصل الثالث :تناولنا فيه «ماهية المؤسسات الرياضية» وأهداف المؤسسات الرياضية والمبادئ الأساسية لإدارة المؤسسة الرياضية ومديرية الشباب والرياضة. الفصل الرابع :والمتمثل في «الإجراءات الميدانية للدراسة»، وتناولنا فيه الدراسات الاستطلاعية، وقد تم تحديد فيه المنهج المتبع والمتغيرات إضافة إلى تحديد عينة البحث وكيفية اختيارها وكذلك الأدوات والتقنيات المستخدمة الفصل الخامس :والذي يتمثل في «عرض النتائج وتفسيرها»، وتم فيه تحليل النتائج المحصل عليها ومناقشة الفرضيات. الفصل السادس : وهو عبارة عن «استنتاجات واقتراحات»، يتم فيه عرض النتائج المحققة وتقديم بعض الاقتراحات. نتائج الدراسة:  يساهم ترشيد القرارات المالية في تحسين عملية التخطيط المالي.  مراقبة القرارات المالية والإشراف على تنفيذها تعتبر الأساس في تصحيح مسار التخطيط المالي.  يساهم العمل بالأهداف المالية إلى الارتقاء بالتخطيط المالي في المؤسسة الرياضية .  وجود عناصر فعالة في المؤسسة توفر قاعدة واسعة للبيانات التي تستخدم في عملية التخطيط المالي. اقتراحات وتوصيات: - من خلال القيام بهذه الدراسة المتواضعة، نقترح التوسع في دراسته أكثر من خلال:  إجراء المزيد من الدراسات والبحوث النوعية حول التخطيط المالي ودوره في تطوير أهداف المؤسسة.  إعادة الدراسة الحالية على قطاعات أخرى للتعرف على أوجه الشبه والاختلاف. كشاف بالإنجليزية Institute: Science and Technology of Physical and Sports Activities Department: Sports Administration and Management Serial Number: Registration number: 201535102328 The student (e): Beljoud Abdel Raouf Discussion date: / Thesis Title: Effectiveness of financial planning and its role in developing sports institutions A field study in the Directorate of Youth and Sports - M'sila State - Message language: Arabic Message type: Master University: University of Mohamed Boudiaf of M'sila Supervision of Professor: Dr. Sherif Hamza Pages: 83 sheets. Letter *. word * PDF. In the CD. Specialization: the management of human resources and sports facilities Summary : in Arabic The design of this study was aimed at identifying the reality of the effectiveness of financial planning and its role in the success of sports institutions at the Directorate of Youth and Sports in the Wilayat of M'sila, and then determining how to use the most important steps that help in preparing a financial plan that enables the success and development of sports institutions. To achieve this, the researcher used the descriptive approach to suitability for this study on a random sample of 30 employees from the Directorate of Youth and Sports in the Wilayat of M'sila. In order to provide information that can be relied upon in making judgments about the effectiveness of financial planning and its role in the success of sports institutions, a questionnaire was applied for that, and after ensuring the validity and reliability of the questionnaire, it was used, and after that the final data were collected and prepared for the statistical analysis. Key words: financial planning, sports institutions. This research came in chapters: Eat: The first chapter: is represented in the "general framework of the study", in which we reviewed the concepts and terminology related to research, defining the problem, how to formulate it, partial questions, the most prominent objectives, clarifying the importance, then the general hypothesis, partial hypotheses and previous and similar studies. Chapter Two: The "theoretical background" in which we dealt with the concept of financial planning, its importance, objectives, stages, types and tools. Chapter Three: In it we dealt with "what sports institutions" and the objectives of sports institutions and the basic principles of running a sports institution and the Directorate of Youth and Sports. Chapter Four: Which is the "field procedures for the study", in which we dealt with the exploratory studies, in which the approach and variables were defined in addition to determining the research sample and how to choose it, as well as the tools and techniques used The fifth chapter: which is represented in "presenting and interpreting the results", in which the results obtained were analyzed and the hypotheses were discussed. Chapter Six: It consists of «conclusions and suggestions», in which the achieved results are presented and some suggestions are made. Results:  Rationalizing financial decisions contributes to improving the financial planning process.  Monitoring financial decisions and supervising their implementation is the basis for correcting the course of financial planning.  Working with financial goals contributes to improving financial planning in the sports institution.  The existence of effective elements in the organization that provide a wide base of data to be used in the financial planning process. Suggestions and recommendations: By doing this modest study, we suggest expanding its study further through:  Conducting more qualitative studies and research on financial planning and its role in developing the organization’s objectives.  Repeat the current study on other sectors to identify similarities and differences.
دراسة ميدانية بمديرية الشباب والرياضة –ولاية المسيلة
Keywords: التخطيط المالي; المؤسسات الرياضية; sports institutions; financial planning